Synergy between glyphosate- and cypermethrin-based pesticides during acute exposures in tadpoles of the common South American Toad Rhinella arenarum - Brodeur, Celine Marie Julie (2014)
The herbicide glyphosate and the insecticide cypermethrin are key pesticides of modern management in soy and corn cultures. Although these pesticides are likely to co-occur in ephemeral ponds or aquatic systems supporting amphibian wildlife, the toxicological interactions prevailing in mixtures of these two pesticides have been little studied. The current study evaluated the toxicity of equitoxic and nonequitoxic binary mixtures of glyphosate- and cypermethrin-based pesticides to tadpoles of the common South American toad, Rhinella arenarum. Two different combinations of commercial products were tested: glyphosate Glifosato Atanor + cypermethrin Xiper and glyphosate Glifoglex + cypermethrin Glextrin. When tested individually, the formulations presented the following 96 h-LC50s: Glifosato Atanor 19.4 mg ae L1 and Glifoglex 72.8 mg ae L1, Xiper 6.8 mg L1 and Glextrin 30.2 mg L1. Equitoxic and non-equitoxic mixtures were significantly synergic in both combinations of commercial products tested. The magnitude of the synergy (factor by which toxicity differed from concentration addition) was constant at around twofold for all tested proportions of the glyphosate Glifoglex + cypermethrin Glextrin mixture; whereas the magnitude of the synergy varied between 4 and 9 times in the glyphosate Glifosato Atanor + cypermethrin Xiper mixture. These results call for more research to be promptly undertaken in order to understand the mechanisms behind the synergy observed and to identify and quantify the extent of its environmental impacts.